2021
DOI: 10.48550/arxiv.2106.03880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Encoding-dependent generalization bounds for parametrized quantum circuits

Matthias C. Caro,
Elies Gil-Fuster,
Johannes Jakob Meyer
et al.

Abstract: A large body of recent work has begun to explore the potential of parametrized quantum circuits (PQCs) as machine learning models, within the framework of hybrid quantum-classical optimization. In particular, theoretical guarantees on the out-of-sample performance of such models, in terms of generalization bounds, have emerged. However, none of these generalization bounds depend explicitly on how the classical input data is encoded into the PQC. We derive generalization bounds for PQC-based models that depend … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In contrast, with PQC, the depth and the number of multi qubit gate seems not to increase so fast, i.e., O(poly(n)) in depth and O(n) of multi qubit gates in nqubit system, although PQC does not guarantee a very precise data loading. In fact the power of expressibility of various type of PQC is under actively investigated [35][36][37][38]. For instance we find ansatz with higher expressibility containing a circuit-block or an all-to-all entangler, depending on the hardware architecture.…”
Section: Depth and The Number Of Multi Qubit Gatementioning
confidence: 91%
“…In contrast, with PQC, the depth and the number of multi qubit gate seems not to increase so fast, i.e., O(poly(n)) in depth and O(n) of multi qubit gates in nqubit system, although PQC does not guarantee a very precise data loading. In fact the power of expressibility of various type of PQC is under actively investigated [35][36][37][38]. For instance we find ansatz with higher expressibility containing a circuit-block or an all-to-all entangler, depending on the hardware architecture.…”
Section: Depth and The Number Of Multi Qubit Gatementioning
confidence: 91%
“…Second, since the noise in the quantum devices seems inevitable, increasing the fidelity of the quantum operations and developing better error correction techniques are of crucial importance. Third, for the variational quantum classifiers, there are already some works trying to measure their representation power [185][186][187][188][189][190]. To find whether there is a separation between these models and their classical counterparts for potential future applications, further studies are highly desirable.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…A natural problem is then to generalize the PAC learning model to quantum learning scenarios. Indeed, notable progress has been made along this direction [27][28][29][30][31][32][33][34][35][36][37]. For example, in reference [28] Chung and Lin have studied the sample complexity of learning quantum channels and demonstrated that we can PAC-learn a polynomial-size quantum circuit with a polynomial number of samples.…”
Section: Introductionmentioning
confidence: 99%